1.5 Tapping the sources of healing. Some themes of distress narratives in towns and villages of contemporary Latvia - Lüse, Agita (AM. Rivista della Società Italiana di Antropologia Medica, 2004)
1.5 Tapping the sources of healing. Some themes of distress narratives in towns and villages of contemporary Latvia